Impact of Genetic Background in Fitness Cost Studies: An Example from Glyphosate-Resistant Palmer Amaranth. Issue 1 (March 2014) - Giacomini, Darci; Westra, Philip; Ward, Sarah M.
Abstract : Since its discovery in 2005, glyphosate-resistant Palmer amaranth has become a major problem for many farmers in the southern United States. One mechanism of resistance found in a Georgia population of glyphosate-resistant Palmer amaranth is amplification of the 5-enolpyruvylshikimate-3-phosphate synthase ( EPSPS ) gene throughout the genome, with some resistant plants containing and expressing more than 100 EPSPS genes. Such high numbers of EPSPS genes and protein production could result in a fitness cost to resistant plants due to (1) metabolic cost of overproduction of this enzyme and (2) disruption of other genes after insertion of the EPSPS gene. A greenhouse experiment was set up to investigate differences in growth and reproduction between glyphosate-susceptible and -resistant Palmer amaranth plants. Measurements included growth rate, plant height/volume ratio, final biomass, photosynthetic rate, inflorescence length, pollen viability, and seed set. This study found no significant fitness costs for plants with the resistance trait. This study also provided a clear example of how controlling for genetic background is important in fitness cost studies and how potentially misleading results can be obtained if only a few fitness traits are measured. These results indicate that glyphosate-resistant Palmer amaranth plants with high EPSPS gene copy numbers are likely to persist in field populations, even in the absence of glyphosate, potentially leading to long-term loss of glyphosate as a control option for Palmer amaranth.